Aer Receptors Influence the Pseudomonas chlororaphis PCL1606 Lifestyle - Arrebola, Eva; Cazorla, Francisco M. (Frontiers in Microbiology, 2020)
Pseudomonas chlororaphis PCL1606 (PcPCL1606) is a rhizobacterium isolated from avocado roots, which is a favourable niche for its development. This strain extensively interacts with plant roots and surrounding microbes and is considered a biocontrol rhizobacterium. Genome sequencing has shown the presence of thirty-one potential methyl-accepting chemotaxis proteins (MCPs). Among these MCPs, two candidates are putative functional aerotaxis receptors, encoded at locus PCL1606_41090 (aer1-1) and locus PLC1606_20530 (aer1-2), that are homologous to the Aer receptor of Pseudomonas aeruginosa strain PaO1. Single- and double-deletion mutants in one or both genes have led to motility deficiencies in oxygen-rich areas, particularly reduced swimming motility compared with that of wildtype PcPCL1606. No differences in swarming tests were detected, and less adhesion by the aer double mutant was observed. However, the single and double mutants on avocado plant roots showed delayed biocontrol ability. During the first days of the biocontrol experiment, the aer-defective mutants also showed delayed root colonization. The current research characterizes the presence of aer transductors on P. chlororaphis. Thus, the functions of the PCL1606_41090 and PCL1606_20530 loci, corresponding to genes aer1-1 and aer1-2, respectively, are elucidated.